Responsiveness of the Ankylosing Spondylitis Disease Activity Score (ASDAS) and clinical and MRI measures of disease activity in a 1-year follow-up study of patients with axial spondyloarthritis treated with tumour necrosis factor α inhibitors. Issue 6 (9th September 2009) - Pedersen, Susanne Juhl; Sørensen, Inge Juul; Hermann, Kay-Geert A; Madsen, Ole Rintek; Tvede, Niels; Hansen, Michael Sejer; Thamsborg, Gorm; Andersen, Lis Smedegaard; Majgaard, Ole; Loft, Anne Gitte; Erlendsson, Jon; Asmussen, Karsten; et al.
Abstract : Objectives: To investigate construct validity and responsiveness of the novel ankylosing spondylitis (AS) disease activity score (ASDAS) in patients with spondyloarthritis (SpA). Methods: In a 46-week prospective longitudinal multicentre study of 60 patients with SpA (80% men, median age 40 years (range 21–62)) treated with tumour necrosis factor α (TNFα) inhibitors (infliximab, n=41; etanercept, n=13; adalimumab, n=6), the responsiveness of ASDAS, conventional clinical measures of disease activity and treatment response and the Berlin MRI sacroiliac joint (SIJ) and lumbar spine inflammation scores were compared. Results: After 22 weeks, 58.3% of the patients were clinical responders (50% or 20 mm reduction in the Bath AS Disease Activity Index (BASDAI)). At baseline, clinical responders had significantly higher median (range) ASDAS than non-responders (4.15 (1.98–6.04) vs 2.99 (2.05–6.19), p=0.008). Changes in ASDAS correlated with changes in clinical measures of disease activity (including BASDAI (ρ=0.76) and C-reactive protein (CRP) (0.79)), MRI SIJ inflammation (0.46) and MRI total inflammation scores (0.34). Patients with higher BASDAI or Assessment of SpondyloArthritis International Society (ASAS) responses obtained more profound reductions in ASDAS. ASDAS had the highest responsiveness with an effect size of 2.04 and a standardised response mean of 1.45, whereas BASDAI (effect size 1.86; standardised response mean 1.36) and CRP (effect size 0.63; standardised response mean 0.70) were less responsive. Linear regression showed that a change in BASDAI of 20 mm or 50% corresponded to a change in ASDAS of 1.38 and 1.95, respectively. Conclusion: ASDAS demonstrates construct validity and high responsiveness during treatment with TNFα inhibitors in patients with SpA. The proposed thresholds for disease activity and treatment response need further validation. Trial registration number NCT00133315.